The Impact of Overinvestment on Environmental, Social and Governance Ratings: Evidence from Chinese Corporations - Cao, Mingyao; Duan, Keyi; Cao, Mingyu; Ibrahim, Haslindar (Asian Academy of Management Journal of Accounting and Finance, 2025)
In an era where sustainability practices face increasing global scrutiny, understanding how investment decisions impact ESG ratings is essential. This study examines the relationship between corporate overinvestment and ESG ratings using data from Chinese corporations between 2012 and 2020. Employing fixed effects models for empirical analysis, the results reveal a significant negative relationship between overinvestment and ESG ratings, particularly affecting the social aspect. These findings highlight the importance of efficient investment management in enhancing corporate ESG performance. The study provides valuable insights for corporations aiming to optimise resource allocation to improve their sustainability outcomes.